2015
DOI: 10.2174/1574889809666141224123303
|View full text |Cite
|
Sign up to set email alerts
|

Liver Growth Factor as a Tissue Regenerating Factor in Neurodegenerative Diseases

Abstract: Liver growth factor (LGF) is a hepatic mitogen purified by our group in 1986. In the following years we demonstrated its activity both in “in vivo” and “in vitro” systems, stimulating hepatocytes mitogenesis as well as liver regeneration in several models of liver injury. Furthermore, we established its chemical composition (albumin-bilirubin complex) and its mitogenic actions in liver. From 2000 onwards we used LGF as a tissue regenerating factor in several models of extrahepatic diseases.The use of Liver gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…According to present results, LGF up-regulated Iba1 protein expression and increased TNF-alpha protein levels. These are two features associated with the transient activation of microglia that were also observed in our in vivo studies [15,19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…According to present results, LGF up-regulated Iba1 protein expression and increased TNF-alpha protein levels. These are two features associated with the transient activation of microglia that were also observed in our in vivo studies [15,19].…”
Section: Discussionsupporting
confidence: 83%
“…The activation of astroglia [51] and microglia by several stimuli promotes the synthesis and secretion of various factors with neuroprotective activity [52][53][54]. Among them, the cytokine TNF-alpha seems to play an important role in the mitogenic cascade of LGF in the liver, as well as in LGF-induced neuroregeneration (reviewed by Gonzalo-Gobernado et al, 2014) [15]. Moreover, several studies have shown the involvement of TNF-alpha in neuronal survival [21,55,56] and neurites outgrowth [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The receptors for the advanced glycation end products (RAGE) located in the endothelium could be good candidates, since AGE products have similar biochemical properties to LGF, i.e., they are mostly albumins bound to glucose, which changes albumin conformation [50]. Moreover, RAGE stimulation elicits the release of TNF-α, which is a cytokine that participates in LGF-mediated proliferation and neuroregeneration [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that LGF is a pleiotropic factor capable of stimulating cell proliferation, and tissue regeneration in hepatic and extrahepatic pathologies [10,11,12,13,14]. The use of LGF as a neural tissue regenerator has been recently protected (Patent No US 2014/8,642,551 B2) [15]. The administration of LGF stimulates the sprouting of DA terminals in the striatum of hemiparkinsonian rats [16,17,18], stimulates the generation of new neurons, and promotes their migration in this experimental model of Parkinson’s disease [17], and its delivery into the brain stimulates the survival of grafted fetal neural stem cells and their differentiation to an endothelial-like phenotype [19].…”
Section: Introductionmentioning
confidence: 99%